MICROWAVE-ASSISTED HYDRODISTILLATION EXTRACTION OF CRUDE OIL FROM ARUMANIS MANGO KERNEL (Mangifera indica L.) - Rahmiyati, Lutfia; Saputri, Desi Riana; Alhanif, Misbahudin; Shifa, Naufal Brain; Akbar, Daffa Ahsanul; Auriyani, Wika Atro; Damayanti, Damayanti; Fahni, Yunita; Sanjaya, Andri; Safitra, Edwin Rizki; Adiwibowo, Muhammad Triyogo; Wicaksono, Rihardian Maulana (JURNAL INTEGRASI PROSES, 2025)
Arumanis mango seeds (Mangifera indica L.) are generally underutilized and still considered agricultural waste. Mango seeds offer various benefits, including antioxidant properties, cholesterol-lowering effects, and natural antibiotic activity. This study aims to determine the yield of mango kernel extract, evaluate the influence of solvent type and extraction time on extraction efficiency, and identify the chemical composition of the extract. The extraction process was carried out using the microwave-assisted hydrodistillation (MAHD) at 375 watts, employing three types of solvents: ethanol, ethyl acetate, and n-hexane, with extraction times of 30, 60, and 90 minutes. The chemical composition of the extracts was analyzed using gas chromatography-mass spectrometry (GC-MS) analysis. The results showed that the highest yield was obtained using ethanol at an extraction time of 30 minutes, yielding 40.342%. Based on GC-MS analysis, in the n-hexane at a 90-minute extraction time, the most abundant fatty acid detected was butyric acid, with a retention time of 14.06 minutes and a peak area of 9.852%. Meanwhile, the most dominant compound was hydroxymethyl furfuraldehyde (HMF), which appeared at a retention time of 22.09 minutes with a peak area of 12.437%.